The Influence of Perceived Organizational Support and Self Efficacy on Work Engagement at PT Bhumi Bhakti Sukses Persada - Conoras, Sagita Noviyandini; Widya Parimita; Agung Wahyu Handaru (LPPM Universitas Negeri Jakarta, 2021)
The purpose of this study is : 1) To find out the description of perceived organizational support, self efficacy, and work engagement of employee in PT Bhumi Bhakti Sukses Persada. 2) To find out the influence of perceived organizational support on work engagement of employee in PT Bhumi Bhakti Sukses Persada. 3) To find out the influence of self efficacy on work engagement of employee in PT Bhumi Bhakti Sukses Persada. 4) To find out the influence of perceived organizational support and self efficacy on work engagement of employee in PT Bhumi Bhakti Sukses Persada. The study used 70 respondents as a sample. Data collection technique using survey methods by distributing questionnaires which then processed with SmartPLS version 3. This research used descriptive and explanatory analysis. The result obtained from PLS analysis show that there is a positive and significant influence between perceived organizational support and self efficacy on work engagement. Variable of perceived organizational support and self efficacy is able to influence of work engagement in employees of PT Bhumi Bhakti Sukses Persada with t-statistical value for the perceived organizational support variable on work engagement (3,638 > 1.96) and signification value of (0.000 < 0.005), for self efficacy variables to work engagement has a t-statistical value of (2,876 > 1.96) and a significance value of (0.004 < 0.05), while for perceived organizational support and self efficacy towards work engagement have a t-statistical value of (21,990 > 1.96) with a value of significance (0.000 < 0.05).Keyword : Perceived Organizational Support, Self Efficacy, Work Engagement, Employee